The Existence Of Palm Oil Middlemen (Tengkulak) And Its Impact On The Presence Of Palm Oil Weighing Scales - Anggara, Agil; Soleh, Ahmad; Febliansa, Muhammad Rahman (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The palm oil plantation sector plays a significant role in Indonesia's economy; however, issues such as price discrepancies and illegal trade often arise. One common phenomenon is the role of middlemen, or